Delayed Subsidence After Rifting and a Record of Breakup for Northwestern Zealandia. Issue 3 (4th March 2019) - Boston, Brian; Nakamura, Yasuyuki; Gallais, Flora; Hackney, Ron; Fujie, Gou; Kodaira, Shuichi; Miura, Seiichi; Kaiho, Yuka; Saito, Saneatsu; Shiraishi, Kazuya; Yamada, Yasuhiro
Abstract: Continental rifting and breakup of eastern Gondwana during the Cretaceous separated northern Zealandia from eastern Australia, but the processes leading to this highly extended and largely submerged block of continental crust are unknown. We acquired and processed multichannel seismic reflection data across northern Zealandia and examine the stratigraphy of the Middleton Basin. We identified a two‐phase formation process for the basin, as evidenced by an unconformity separating two postrift units. After initial basin formation and slow deposition of the lower postrift unit, deposition rates within the Middleton Basin rapidly increased in response to the latest stage of subsidence and to create the modern basin. We propose a tectonic model wherein the Middleton Basin initiated through oceanic spreading and the subsequent postrift subsidence of the newly created oceanic lithosphere was delayed due to thermal buoyancy associated with nearby oceanic spreading in the Tasman Basin. Our results provide new constraints on rifting and breakup processes of wide, magma‐poor, and asymmetric margins and indicate that multiple regions of weak lithosphere may have influenced the breakup. Plain Language Summary: Tens of millions of years ago, an elongate continental fragment now known as Zealandia broke away from eastern Australia. Because most of Zealandia is underwater in a remote part of the southwest Pacific, little is known about the processes that led to its submergence and isolation. We have used a common subsurface imaging technique based on sound waves bouncing off deep rock layers to map sediments below the seafloor that record the geological events leading to the formation of Zealandia. Our focus is on the Middleton Basin, an elongate trough between two continental blocks that has a uniquely flat seafloor and is filled with up to 3.5 km of sediments. Our results suggest that the geological history of the Middleton Basin initially involved formation of a new, narrow ocean between two continents—like the Red Sea today. Ocean formation then jumped further to the west, ultimately resulting in the wide and deep Tasman Sea. This stop‐start formation of two new oceans during the fragmentation of a continent is uncommon and highlights Zealandia's role in revealing the intriguing geological history of Earth's continents. Key Points: Thick postrift sediments covering the oceanic Middleton Basin are divided by an unconformity indicative of delayed subsidence This delayed subsidence resulted from dynamic support linked to hot mantle associated with later spreading in the adjacent Tasman Basin This dual ocean basin formation suggests that multiple zones of lithospheric weakness affected the breakup of the eastern Gondwana margin